2019
DOI: 10.1590/1981-6723.19318
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated fatty acids and nutritional quality of five freshwater fish species cultivated in the western region of Santa Catarina, Brazil

Abstract: There is a paucity of information about the chemical composition of commercially important freshwater fish species (Nile tilapia, bighead carp, grass carp, common carp and silver carp) cultivated in the western region of Santa Catarina, Brazil. This study determined the moisture, ash, protein and lipid contents and the fatty acid composition, as well as the nutritional quality of the lipids in fillets of these five freshwater fish species. Moisture was the most prominent fish component (74.7%-81.7%), followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 31 publications
3
17
0
1
Order By: Relevance
“…The dominant SFA acids were stearic acid and palmitic acid, while elaidic acid and linolenic acid were the major MUFA and PUFA. Similar results were reported by Matos et al (2019) who found 380 mg/100 g SFA, 300 mg/100 g MUFA, 30 mg/100 g PUFA, 40 mg/100 g n-3 and 10 mg/100 g n-6 in pond-cultured tilapia and 1,250 mg/100 g SFA, 1570 mg/10 0g MUFA, 550 mg/100 g PUFA, 60 mg/100 g n-3 and 490 mg/100 g n-6 in cage-cultured tilapia. Similar results for tilapia from the local fish markets in Poland were reported by Usydus et al (2011) who found 35.4% SFA, 33.1% MUFA, 31.5% PUFA, 9.9% n-3 and 21.6% n-6.…”
Section: Fatty Acid Compositionsupporting
confidence: 92%
See 3 more Smart Citations
“…The dominant SFA acids were stearic acid and palmitic acid, while elaidic acid and linolenic acid were the major MUFA and PUFA. Similar results were reported by Matos et al (2019) who found 380 mg/100 g SFA, 300 mg/100 g MUFA, 30 mg/100 g PUFA, 40 mg/100 g n-3 and 10 mg/100 g n-6 in pond-cultured tilapia and 1,250 mg/100 g SFA, 1570 mg/10 0g MUFA, 550 mg/100 g PUFA, 60 mg/100 g n-3 and 490 mg/100 g n-6 in cage-cultured tilapia. Similar results for tilapia from the local fish markets in Poland were reported by Usydus et al (2011) who found 35.4% SFA, 33.1% MUFA, 31.5% PUFA, 9.9% n-3 and 21.6% n-6.…”
Section: Fatty Acid Compositionsupporting
confidence: 92%
“…(2011) reported 2% lipid, 16.4% protein, 81.2% moisture and 0.5% ash in tilapias collected from local fish markets in Poland. In addition, Matos et al. (2019) reported 77.8%–79.7% moisture, 18.1%–18.8% protein, 1%–3.6% lipid and 0.9%–1.2% ash in cage- and pond-cultured tilapia respectively.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Mohanty et al (2019) evaluated the moisture content for four different carnivorous species (singhi, magur, murrels and koi), which ranged between 65% and 80%. Similar investigations were carried out by Matos et al (2019) on five different fish species, with the results ranging between 74.7% and 81.7%. Hussain et al (1992) observed the moisture content in Labeo ghonius ranged widely from 12.3% to 54.0%.…”
Section: Resultssupporting
confidence: 82%